Human regulatory macrophages are potent in suppression of the xenoimmune response via indoleamine‐2, 3‐dioxygenase‐involved mechanism(s). (2nd August 2017) - Guo, Fei; Hu, Min; Huang, Dandan; Zhao, Yuanfei; Heng, Benjamin; Guillemin, Gilles; Lim, Chai K.; Hawthorne, Wayne J.; Yi, Shounan
Abstract: Background: For xenotransplantation to truly succeed, we must develop immunomodulatory strategies to suppress the xenoimmune response but by minimizing immunosuppression over the long term. Regulatory macrophages (Mreg) have been shown to suppress polyclonal T‐cell proliferation in vitro and prolong allograft survival in vivo. However, the question of whether they are capable of suppressing xenoimmune responses remains unknown. This study assessed the potential of human Mreg to be used as an effective immunomodulatory method in xenotransplantation. Methods: CD14+ monocytes selected from human peripheral blood mononuclear cells (PBMC) were cultured with macrophage colony‐stimulating factor (M‐CSF) for 7 days with IFN‐γ added at day 6 for Mreg induction. Mreg phenotyping was performed by flow cytometric analysis, and the in vitro suppressive function was assessed by mixed lymphocyte reaction (MLR) using irradiated pig PBMC as the xenogeneic stimulator cells, human PBMC as responder cells, and autologous Mreg as suppressor cells. To assess mRNA expression of Mreg functional molecules indoleamine‐2, 3‐dioxygenase (IDO), IL‐10, inducible nitric oxide synthase (iNOS) and TGF‐β were measured by real‐time PCR. Supernatants were collected from the MLR cultures for IDO activity assay by high‐performance liquid chromatography (HPLC). The effects of the IDO inhibitor 1‐D/L‐methyl‐tryptophan (1‐MT), iNOS inhibitor N G ‐monomethyl‐l‐arginine (L‐NMMA), and anti‐IFN‐γ or anti‐TGF‐β monoclonal antibody (mAb) treatment on Mreg suppressive capacity were tested from the supernatants of the MLR assays. Results: We demonstrated that induced Mreg with a phenotype of CD14 low CD16 −/low CD80 low CD83 −/low CD86 +/hi HLA‐DR +/hi were capable of suppressing proliferating human PBMC, CD4+, and CD8+ T cells, even at a higher responder:Mreg ratio of 32:1 in a pig‐human xenogeneic MLR. The strong suppressive potency of Mreg was further correlated with their upregulated IDO expression and activity. The IDO upregulation of Mreg was associated with an increased production of IFN‐γ, an IDO stimulator, by xenoreactive responder cells in the xenogeneic MLR. While no effect on Mreg suppressive potency was detected by addition of the iNOS inhibitor L‐NMMA or anti‐TGF‐β mAb into the MLR assays, inhibition of IDO activity by neutralizing IFN‐γ or by IDO inhibitor 1‐MT substantially impaired the capacity of Mreg to suppress the xenogeneic response, indicating the importance of upregulated IDO activity in Mreg‐mediated suppression of the xenogeneic response in vitro. Conclusion: This study demonstrates that human Mreg are capable of suppressing the xenoimmune response in vitro via IDO‐involved mechanism(s), suggesting their potential role as an effective immunomodulatory tool in xenotransplantation.